Economic Adaptation to Change in Reindeer Herding in Sakha (Yakutia) - Pogodaev, Mikhail (2009)
Outline of the challenges facing reindeer husbandry in te Republic of Sakha (Yakutia), a region that will experience a great deal of industrial development should plans on the table go through